2017
DOI: 10.1159/000478526
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cortisol Concentration in Scalp Hair of Asthmatic Children Using Inhaled Corticosteroids: A Case-Control Study

Abstract: Introduction: Inhaled corticosteroids (ICS) can interfere with the hypothalamic-pituitary-adrenal (HPA) axis and may lead to adrenal insufficiency, resulting in a decrease of cortisol production. Cortisol levels measured in scalp hair provide a marker for long-term cortisol exposure. Data regarding hair cortisol concentration (HCC) in asthmatic children with ICS therapy are scarce. The aim of this study is to compare HCC in asthmatic children under ICS treatment with a healthy control group. Methods: We set up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…We measured the association between ICS and HCC in chronic ICS users who had been using ICS for a period of at least 2 years. Like in our study, Smit et al investigated the effect of ICS dose on HCC in a cross‐sectional design including 80 asthmatic children, and also did not see a significant dose effect. We observed that the median HCC was lower by increasing ICS dose categories (low, medium, and high) but this difference in median HCC did not reach statistical significance probably because of low numbers, especially of patients using high dose ICS, and the variety in sensitivity to glucocorticosteroids.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…We measured the association between ICS and HCC in chronic ICS users who had been using ICS for a period of at least 2 years. Like in our study, Smit et al investigated the effect of ICS dose on HCC in a cross‐sectional design including 80 asthmatic children, and also did not see a significant dose effect. We observed that the median HCC was lower by increasing ICS dose categories (low, medium, and high) but this difference in median HCC did not reach statistical significance probably because of low numbers, especially of patients using high dose ICS, and the variety in sensitivity to glucocorticosteroids.…”
Section: Discussionsupporting
confidence: 64%
“…The samples were sent to the Department of Clinical Chemistry, Erasmus MC, Rotterdam, The Netherlands. The samples were processed and analyzed as described previously . The proximal 3 cm of hair were used for analyses.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations